(untitled) (SCIÉNDO INGENIUM, 2022)
Designing organizations is the process by which the structure of an organization was built in order to achieve objectives. The detailed bibliographic search the presence of conceptual references to this topic; but no experiences on the design process applied to MYPES. The work has been divided into two important parts for the success or failure of the organization: In the first part, the difficulties that MYPES present in the elaboration of their organizational design are described, which includes the establishment of an intentional structure of roles and responsibilities for collaborators, which allow identifying all the tasks necessary to achieve the objectives. In the second part, an organizational design model was presented for MYPES in the Mining sector in Peru, which identifies the activities necessary for an efficient organizational structure. In this sense, the organizational design used as a technique observation and instruments, a check-list, a satisfaction test based on Likert and NPS, with which it was possible to improve from 37% to 94%, it is evident that the structure of the organizational design must be based on regulatory principles, which allows to see its profitability improved up to 87,5% ( 189 069,99).